Food supplement based on whey protein isolate, probiotic and β-glucan: effects on anthropometric measurements and immunity in women (Research, Society and Development, 2020)
The food market with functional properties is growing, and this segment is closely related to innovations. In this sense, products containing whey proteins, popularly known as “Whey Protein”, are gaining more and more space in the food supplement market. The objective of this work was to elaborate a food supplement based on whey protein isolate, probiotic Bifidobacterium lactis HN019 and β-glucan and to evaluate its effects on anthropometric parameters and levels of salivary immunoglobulin (IgA) in women practicing physical activity. The study was carried out with 24 women, mean age 61 years, with a 15-minute stretching routine and 45 minutes between aerobic and resistance exercises. The food supplement was administered once a day, for 90 days. Anthropometric assessments (supra iliac, abdomen (mm), chest, waist, hips, waist circumference (cm), % fat, lean body mass and fat weight) were performed before, during and after supplementation. The determination of salivary IgA was performed in the same periods. The results showed that supplementation combined with a physical exercise routine significantly improved (p